EFFECT OF PROMOTION, BRAND IMAGE, AND PRODUCT QUALITY ON RE-PURCHASE INTEREST THROUGH CUSTOMER SATISFACTION AS INTERVENING ON ERIGO APPAREL PRODUCTS - Arif Fathurahman, Ade; Janfry Sihite (Dinasti International Journal of Management Science, 2022)
Through Customer Satisfaction as an Intervention on Erigo Apparel Products, this study will examine the effect of promotion, brand image, and product quality on repurchase interest. The study's subject was an Erigo Apparel customer. A total of 94 students and schoolgirls from Negeri 7 South Tangerang City participated in the study. Simple random sampling technique is used to determine sample size. The Structural Equation Model (SEM) with the Smart-PLS analysis tool was employed in this investigation. According to the findings of this study, promotion has a positive and significant impact on customer satisfaction, brand image has a positive and significant impact on customer satisfaction, product quality has a positive and significant impact on customer satisfaction, promotion has a negative but significant impact on repurchase interest, brand image has a positive and significant impact on repurchase interest, and product quality has a positive and significant impact on repurchase interest. Customer satisfaction can mediate marketing against re-purchase interest, but it can't mediate brand image against re-purchase interest. Customer satisfaction can mediate product quality against re-purchase interest, and it can influence re-purchase interest positively and considerably.